Improving the crashworthiness of CFRP structures by rubbery nanofibrous interlayers. (1st May 2023) - Falaschetti, Maria Pia; Rondina, Francesco; Maccaferri, Emanuele; Mazzocchetti, Laura; Donati, Lorenzo; Zucchelli, Andrea; Giorgini, Loris
Abstract: Crashworthiness is the capability of a component to dissipate impact energy throughout its deformation and failure. Composite materials are used to produce crashworthy components to ensure vehicle safety, thanks to their ability to dissipate a high energy amount while maintaining a low weight. The present work investigates the integration of rubbery nanofibers within the laminate interlayers to enhance crush performance. Three different thicknesses (10, 20, and 40 µm) of nanofibrous mats made by nitrile butadiene rubber and polycaprolactone (NBR/PCL) blends were produced by single-needle electrospinning technique and integrated into the laminates during the hand-layup. Mechanical properties of the nano-modified laminates are compared to the reference configuration: the effect of the interlayers is evaluated by Double Cantilever Beam (DCB) and End-Notched Flexure (ENF) interlaminar fracture tests. At the same time, the specific crush energy absorption (SEA) is measured by the compression of self-supporting corrugated specimens. Results show that NBR/PCL nanofibers significantly increase the interlaminar fracture toughness (up to +254% for Mode I and +47% for Mode II), which ultimately helps to improve the total SEA up to +8.2%. The best SEA enhancement is achieved already with a 10 µm nanofibrous membrane while integrating the highest thickness mat has a detrimental effect.